Synthesis and Characterization of Psychopharmacologically Active Complexes of Copper(II) and Zinc(II) with 2-(Furan-2-formylimino)benzimidazole - Jose, C.V.; Sharma, L.M.; Joy Anto, T. (Asian Journal of Chemistry, 2016)
Synthesis of Cu(II) and Zn(II) complexes with 2-(furan-2-formylimino)benzimidazole having ML2X2 stoichiometries have been reported (where X = Cl–, NO3–, CH3COO– and C6H5COO–). Characterizations have been done on the basis of elemental analysis, conductivity, magnetic, IR and electronic spectral studies. Complexes have been found psychopharmocologically more effective in taming and hypnotic activities and possess much higher toxicity as compared to the ligand.